Differentiation of human neural progenitor cell-derived spiral ganglion-like neurons: a time-lapse video study. (May 2014) - Edin, Fredrik; Liu, Wei; Boström, Marja; Magnusson, Peetra U.; Rask-Andersen, Helge
Abstract: Conclusions: Human neural progenitor cells can differentiate into spiral ganglion-like cells when exposed to inner ear-associated growth factors. The phenotype bears resemblance to human sphere-derived neurons. Objective: To establish an in vitro model for the human auditory nerve to replace and complement in vivo animal experiments and ultimately human in vivo transplantation. Methods: Human neural progenitors were differentiated under conditions developed for in vitro survival of human primary spiral ganglion culture with media containing growth factors associated with inner ear development. Differentiation was documented using time-lapse video microscopy. Time-dependent marker expression was evaluated using immunocytochemistry with fluorescence and laser confocal microscopy. Results: Within 14 days of differentiation, neural progenitors adopted neural phenotype and expressed spiral ganglion-associated markers.